A story of the missing parotid: case report and systematic review of literature - Rekhade, Tanvi Shirish; Mahore, Devendra; Patel, Seema (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Anatomic variations of the parotid gland are rare. We present the case of a 69-year-old male who presented with unilateral slow growing left sided cheek swelling. Radiological imaging revealed buccal space masses with characteristics similar to those of a salivary gland. Of particular note was the radiological absence of the left parotid gland. Due to the diagnostic uncertainty of this unusual presentation, the patient underwent surgical excision. An intraoral approach was utilized, with careful consideration of the facial nerve’s course. Istopathological examination confirmed the diagnosis of a pleomorphic adenoma (PA) of ectopic parotid tissue. A thorough review of literature in PubMed and Google revealed only four previously reported cases, prompting us to include a brief systematic review. Given the rarity of ectopic parotid cases, it is often a diagnosis of exclusion. However, the occurrence of PA within ectopic parotid tissue underscores its importance in the differential diagnosis of unilateral cheek swelling.